2017
DOI: 10.1055/s-0042-107915
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Hypotonie: Bedeutung und Monitoring in der klinischen Praxis

Abstract: Zusammenfassung Intraoperative Hypotonie ist im klinischen Alltag keine Seltenheit. Obwohl ein Zusammenhang mit erh?hter perioperativer Morbidit?t und Letalit?t zu bestehen scheint, wird sie oft zu sp?t oder gar nicht therapiert. Dabei gibt es eine Vielzahl an Pr?diktoren und technischen Hilfsmitteln, um Risikopatienten zu identifizieren und das perioperative Management durch ein ad?quates Monitoring und eine fr?hzeitige Therapie zu optimieren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…As there is no general consensus regarding optimal blood pressure targets, the minimum target SBPmin was defined here on a case by case basis by the treating physician. Recent studies indicated that individualized blood pressure management may in fact be preferable compared with a more standard strategy using predefined threshold values [18,19]. While numerically higher AUC values were observed in patients treated with C/T, these values were not significantly different between treatment arms; however, when evaluating the AUC data it must be taken into account that these values reflect not only the course of SBP but also the targeted increase in SBP.…”
Section: Discussionmentioning
confidence: 99%
“…As there is no general consensus regarding optimal blood pressure targets, the minimum target SBPmin was defined here on a case by case basis by the treating physician. Recent studies indicated that individualized blood pressure management may in fact be preferable compared with a more standard strategy using predefined threshold values [18,19]. While numerically higher AUC values were observed in patients treated with C/T, these values were not significantly different between treatment arms; however, when evaluating the AUC data it must be taken into account that these values reflect not only the course of SBP but also the targeted increase in SBP.…”
Section: Discussionmentioning
confidence: 99%